PERANCANGAN SISTEM & USER INTERFACE UNTUK APLIKASI KASIR DAN INVENTARIS PADA BENGKEL BARU MOTOR SPORT - Rafael Wun; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
An easy-to-use and efficient interface is essential for cashiering and inventory management systems, especially in motorcycle workshops that have unique requirements for tracking goods and processing sales transactions. This research focuses on designing a web-based application interface to streamline sales transactions and inventory management at the Baru Motor Sport workshop. The User Interface (UI) simplifies core processes, including recording incoming and outgoing goods, managing inventory, and processing sales transactions in real-time. Vue.js is used to create a responsive and intuitive front-end, supported by Tailwind CSS for a modern design. The design process followed the Scrum methodology, which emphasizes iterative feedback, flexibility, and continuous improvement to align the UI with user needs. The interface accommodates three main roles: Admin, Inventory Staff, and Cashier Staff. Each role's UI is customized to facilitate user-specific tasks, such as inventory tracking for Inventory Staff and transaction handling for Cashier Staff, while Admin oversees user management and views sales reports. This UI design aims to improve operational efficiency, enhance usability, and support accurate and efficient workflows in the workshop.